Comparative Study of Bisection, Newton, Horner’s Method for Solving Nonlinear Equation - Amiruddin Ab Aziz; Nur Afriza Baki; Abdul Zaki Bin Zamri Azuha; Mohamad Aliff Haziq (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2021)
The Bisection, Newton and Horner’s method are used to compare the efficiency to solve nonlinear function such as trigonometric, exponential, logarithmic and cubic polynomial function. Although these methods are considered as alternative, the methods also possess error compared to the exact value. The efficiency is measured by the error produced at the fixed iteration. The methods are converted into C language and executed by using maple 18.